2-(3, 4-Epoxy) ethyltriethoxysilane-modified waterborne acrylic resin: Preparation and property analysis. (2nd March 2020) - Jiao, Cuiyan; Shao, Qian; Wu, Mingyang; Zheng, Bin; Guo, Zhen; Yi, Jimin; Zhang, Jiaoxia; Lin, Jing; Wu, Shide; Dong, Mengyao; Guo, Zhanhu
Abstract: Waterborne acrylic resin was prepared by emulsion polymerization (copolymerization of all acrylic monomers) and was modified by 2-(3, 4-epoxy) ethyltriethoxysilane (KH567). The effects of KH567 on the properties of waterborne acrylic resin were investigated from the aspects of mechanical properties, thermal stability, and hydrophobicity. Fourier transform infrared spectroscopy (FTIR) analysis indicated that KH567 was grafted onto the molecular chain of acrylic resin. Differential scanning calorimetry (DSC) analysis showed that the curing temperature of the resin/KH567 (56.09 °C) was lower than that of pure resin (70.07 °C). Moreover, the contact angle of coating film increased to 90.4°. Additionally, the addition of KH567 could reinforce the spatial structure and increase the crosslinking density, and thus improved the tensile strength of the coating films properly while keeping other performances well. The work provides a simple way for the performance optimization of waterborne acrylic resin and represents a tendency for environmental friendly resin. Graphical abstract: Image 1 Highlights: A novel waterborne acrylic resin was prepared. 2-(3, 4-epoxy) ethyltriethoxysilane (KH567) was used to modify the resin. The addition of KH567 improved the hydrophobicity of resin coating. The mechanical property of the modified resin coating was markedly enhanced.